Dental Age Estimation Of Malaysian Chinese Children And Adolescents: Chaillet And Demirjian's Method Revisited Using Artificial Multilayer Perceptron Neural Network - Safar Sumit Bunyarit; Jayakumar Jayaraman; Murali K. Naidu; Rozaida Poh Yuen Ying; Phrabhakaran Nambiar; Muhammad Khan Asif (Taylor & Francis, 2024)
Indexed by ERA